Cadmium distribution and soil properties across soil orders under cacao (Theobroma cacao L.) cultivation in the Peruvian Amazon - Vallejos-Torres, Geomar; Chuchon-Remon, Rodolfo; Gaona-Jimenez, Nery; Cruz-Luis, Juancarlos; Solórzano-Acosta, Richard (Frontiers in Soil Science, 2025)
IntroductionHigh cadmium (Cd) levels in Peru are limiting access to international markets that have implemented stricter thresholds for allowable concentrations in chocolate and its derivatives. This study aimed to analyse the distribution of cadmium profiles and their edaphic controls across different soil orders under cacao (Theobroma cacao L.) cultivation in the Peruvian Amazon.terms.MethodsThe research was conducted in three locations within two districts of the San Martín department, encompassing an area of 4,073.54 km². The study sites included the towns of La Unión and Nuevo San Martín in the Pólvora district (Tocache province) and the town of Perla Mayo in the Campanilla district (Mariscal Cáceres province). In each locality, ten 100 m² plots were selected, resulting in a total of 30 plots. Soil samples were collected by excavating pits measuring 1 × 0.8 m, with samples taken from two depth intervals: 0–30 cm and 30–60 cm.ResultsTotal cadmium concentrations and key physicochemical parameters were then analysed. The soils in La Unión exhibited the highest average Cd concentrations at 0–30 cm depth (1.35 ± 0.21 mg/kg), while the lowest concentrations were recorded in Perla Mayo at the same depth (0.27 ± 0.25 mg/kg). Regarding soil classification, Entisols and Alfisols presented the lowest average Cd contents (0.66 ± 0.35 mg/kg and 0.15 ± 0.15 mg/kg, respectively). Among the evaluated soil properties, cation exchange capacity (CEC) and clay content were identified as the primary factors influencing cadmium levels, followed by soil pH.DiscussionThe cadmium tends to accumulate in the surface horizons of fine-textured, acidic soils at each study site. The edaphic conditions in Perla Mayo appear to be the most favourable, showing minimal cadmium accumulation, and may serve as a reference for developing agricultural management strategies aimed at reducing cadmium uptake in cacao-growing soils.